2020
DOI: 10.1002/btpr.3088
|View full text |Cite
|
Sign up to set email alerts
|

Adapting virus filtration to enable intensified and continuous monoclonal antibody processing

Abstract: Ongoing efforts in the biopharmaceutical industry to enhance productivity and reduce manufacturing costs include development of intensified, linked, and/or continuous processes. One approach to improve productivity and process economics of the polishing step (i.e., anion exchange chromatography) is to preconcentrate the product intermediate using a single-pass tangential flow filtration step before loading on the resin. This intensification of the polishing step consequently leads to changes in product interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…It was found that low flux conditions could lead to a reduction of the virus retention of 20 L/m 2 bacteriophages spiked mAb feed solutions with some of the commercial filters. On the other hand, another recent 4.5 LMH constant flux virus filtration study (Bohonak et al, 2020) with a more viscous feed at high product titer did not exhibit MVM breakthrough. These studies support the important role of diffusion plays in virus filtration at low‐pressure low flux conditions.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…It was found that low flux conditions could lead to a reduction of the virus retention of 20 L/m 2 bacteriophages spiked mAb feed solutions with some of the commercial filters. On the other hand, another recent 4.5 LMH constant flux virus filtration study (Bohonak et al, 2020) with a more viscous feed at high product titer did not exhibit MVM breakthrough. These studies support the important role of diffusion plays in virus filtration at low‐pressure low flux conditions.…”
Section: Resultsmentioning
confidence: 82%
“…Diffusion appears to play an important role in virus retention for Filter V particularly when longer filtration time is needed at such a low flux. An earlier study (Bohonak et al, 2020) shows that a low flux at 4.5 LMH did not lead to virus breakthrough. This is likely due to the fact that particle diffusion is restricted with a more viscose feed stream at a product titer of 50 g/L.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…PQ surge tank was used to homogenize output from the AEX step and make it ready for the VF step. Although there were publications about performing low‐pressure VF in a continuous process, [ 18,19 ] VF in this work was carried out in the same way as the batch process. This manner was chosen for two reasons.…”
Section: Resultsmentioning
confidence: 99%